Context of Rural to Urban Migration and Socio-Economic Empowerment of Women in Pakistan and Philippines; a Systematic Literature Review - Ram, Meetha; Nizamani, Bakhtawar; Fateh Muhammad, Aazadi (Universitas Cokroaminoto Yogyakarta, 2025)
The movement of people from rural areas towards urban units is understood as rural-to-urban migration. Women empowerment is the process that leads women to ownership of resources, improves their ability to control their lives and families, and allows them to make decisions to develop new strategies in life. The rural-to-urban migration in Pakistan changes the socioeconomic status of women through their engagements in formal job markets and increases earning sources through paid or professional work. In the Philippines, the economic driver is one of the primary and dominant forces for rural-to-urban migration. This study aimed to assess the impacts of migration on women’s socio-economic status. Also, it focused on exploring migration trends and women’s engagement in the labour market after migration in both countries.